Donkey-assisted therapy in mental health conditions: a systematic review - Fulgenzi, Alessia; Raffa, Antonio; De Domenico, Carmela; Di Cara, Marcella; Leonardi, Simona; Piccolo, Adriana; Giambò, Fabio Mauro; Marafioti, Giulia; Alito, Angelo; Leonardi, Giulia; Turriziani, Laura; Panzera, Michele; et al. (Frontiers in Psychiatry, 2025)
IntroductionThis paper evaluates the effectiveness of donkey-assisted therapy in neurodevelopmental disorders in children, adolescents, and adults.MethodsRegistered in the PROSPERO database (CRD42025644921) and conducted according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses, the review included studies from ScienceDirect (Elsevier), Web of Science, and PubMed (National Library of Medicine), searched up to 31 December 2024. The inclusion criteria were (a) pilot studies, randomized control studies, and uncontrolled clinical trials, (b) dealing with donkey-assisted interventions (DAI) in children, adolescents, and adults age, (c) in English, Italian, Spanish, or German languages. The exclusion criteria were: (a) clinical cases, pre-prints, letters to the editor, reviews, and systematic reviews; (b) studies involving therapies other than donkey-assisted therapy.ResultsFour observational studies were included. The results suggest that donkey-assisted interventions, particularly donkey-assisted therapy, help improve emotional regulation, communication, social interaction, and self-esteem in children with neurodevelopmental disorders. Improvements in autonomy, motor coordination, and social engagement have been observed in adults.ConclusionThe heterogeneity of study methodologies, variations in sample size, assessment instruments, and intervention duration limit the generalizability of the results. Future research should focus on large-scale, well-controlled studies, standardizing protocols and outcome measures to quantify the therapeutic impact of DAI in diverse populations.